2015
DOI: 10.1111/acem.12799
|View full text |Cite
|
Sign up to set email alerts
|

Using Video‐recorded Laryngoscopy to Evaluate Laryngoscopic Blade Approach and Adverse Events in Children

Abstract: Objectives: Using recordings of endotracheal intubation attempts obtained with a video-enabled laryngoscope with Miller and Macintosh blades, the authors sought to evaluate the association between laryngoscopic approach (right-sided vs. midline) and intubation success, as well as adverse event rates in the pediatric emergency department (ED).Methods: This was a retrospective cohort study of children younger than 21 years who underwent endotracheal intubation with a C-MAC video laryngoscope in a tertiary care E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…A final potential benefit of the C‐MAC is that it allows intubation attempts to be recorded and later reviewed for educational purposes and to assess performance metrics such as number of attempts, time to intubation, and complications . This method of QA allows for both impartiality and expert review of the procedure, a substantial improvement over self‐report.…”
Section: Discussionmentioning
confidence: 99%
“…A final potential benefit of the C‐MAC is that it allows intubation attempts to be recorded and later reviewed for educational purposes and to assess performance metrics such as number of attempts, time to intubation, and complications . This method of QA allows for both impartiality and expert review of the procedure, a substantial improvement over self‐report.…”
Section: Discussionmentioning
confidence: 99%
“…3,[12][13][14][15][16][17][18] In the face of this challenge, we developed our curriculum through the construct of learn, see, practice, prove, do, maintain, progressing learners through variable learning modalities and exposing them to novel airway educational interventions such as the use of real patient laryngoscopy videos. 14,15,[19][20][21][22] As such, our curriculum differs from existing resources and thereby offers a unique contribution to the literature as it offered extensive resources specific to pediatrics, highlighted the video laryngoscope as both a patient safety and educational adjunct, and provided learners multiple opportunities to apply their understanding of key concepts through both deliberate practice, coaching, and simulation. 12,19,[23][24][25] While components of our curriculum can be implemented with any learner along the medical education continuum, we have targeted our curriculum to the following learners: senior pediatric residents, pediatric emergency medicine fellows, pediatric intensive care fellows, emergency medicine residents, critical care transport paramedics and community hospital emergency medicine physicians, physician assistants, and nurse practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain adequate direct visualization during intubation, the tongue is commonly swept to the left according to guidance [4, 13]. Although the midline approach has been proposed for intubation by some experts in the early twentieth century, they point to direct laryngoscopy not video laryngoscopy [5, 1315]. Additionally, no clear evidence exists to support the clinical experience until now.…”
Section: Discussionmentioning
confidence: 99%
“…The midline approach without sweep of the tongue is commonly recommended to achieve an unobstructed view of the larynx by VL, but there is a lack of published supporting evidence. Israel and colleagues conducted a retrospective cohort study of children who had undergone endotracheal intubation using VL and found no difference in successful intubation on the first attempt based on the laryngoscopic approach type [5]. However, many factors, including glottis visualization, pre-shaped angulation of the tube, level of trainee and presence of difficult airway predictors, are all correlated with first-pass success (FPS) [68].…”
Section: Introductionmentioning
confidence: 99%